2016
DOI: 10.12688/f1000research.10414.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antiretroviral therapy on clinical outcomes in HIV+ kidney transplant recipients: Review of 58 cases

Abstract: Background: Antiretroviral therapy (ART) poses challenging drug-drug interactions with immunosuppressant agents in transplant recipients.  We aimed to determine the impact of specific antiretroviral regimens in clinical outcomes of HIV + kidney transplant recipients.  Methods: A single-center, retrospective cohort study was conducted at a large academic center. Subjects included 58 HIV - to HIV + adult, first-time kidney transplant patients. The main intervention was ART regimen used after transplantation.  Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
(29 reference statements)
4
17
0
Order By: Relevance
“…We have also reported that individuals receiving HIV PIs had a higher incidence of serious infections compared to those on PI‐sparing regimens (39% vs 8%, P = 0.01), which might explain why serious infections (and associated poor outcomes) in the present study were exclusively seen among patients in the pre‐DAA era, as most of them received PI‐based ART regimens . The increased risk of serious infections in PI‐treated patients could be related to increased exposure to immunosuppressants . Supporting this notion, we observed that three out of four PI‐treated patients with serious infections had supra‐therapeutic tacrolimus levels at the time of infection.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We have also reported that individuals receiving HIV PIs had a higher incidence of serious infections compared to those on PI‐sparing regimens (39% vs 8%, P = 0.01), which might explain why serious infections (and associated poor outcomes) in the present study were exclusively seen among patients in the pre‐DAA era, as most of them received PI‐based ART regimens . The increased risk of serious infections in PI‐treated patients could be related to increased exposure to immunosuppressants . Supporting this notion, we observed that three out of four PI‐treated patients with serious infections had supra‐therapeutic tacrolimus levels at the time of infection.…”
Section: Discussionsupporting
confidence: 78%
“…In a previous study, we have reported a higher incidence of serious infections in HIV+/HCV+ coinfected than in HIV‐monoinfected patients (80% vs 25%, P = 0.03) . We have also reported that individuals receiving HIV PIs had a higher incidence of serious infections compared to those on PI‐sparing regimens (39% vs 8%, P = 0.01), which might explain why serious infections (and associated poor outcomes) in the present study were exclusively seen among patients in the pre‐DAA era, as most of them received PI‐based ART regimens . The increased risk of serious infections in PI‐treated patients could be related to increased exposure to immunosuppressants .…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Kidney transplant outcomes in the HAART era are similar between HIV-positive and negative patients with the 3-year patient and graft survival of 90%. 4,5 Similar outcomes have been reported in liver transplantation with equivalent 1-, 3-, and 5-year patient and graft survival rates between HIV-positive and negative liver transplant recipients. 6 Orthotopic heart transplantation (OHT) is rarely performed in HIVpositive patients despite the fact that HIV-associated cardiomyopathy is a major long-term complication of HIV infection.…”
Section: Introductionsupporting
confidence: 62%
“…Kidney and liver transplants are performed often among HIV‐positive patients with excellent outcomes. Kidney transplant outcomes in the HAART era are similar between HIV‐positive and negative patients with the 3‐year patient and graft survival of 90% 4,5 . Similar outcomes have been reported in liver transplantation with equivalent 1‐, 3‐, and 5‐year patient and graft survival rates between HIV‐positive and negative liver transplant recipients 6 …”
Section: Introductionsupporting
confidence: 53%